If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 49x + 1.5 = 25x + 3 Reorder the terms: 1.5 + 49x = 25x + 3 Reorder the terms: 1.5 + 49x = 3 + 25x Solving 1.5 + 49x = 3 + 25x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25x' to each side of the equation. 1.5 + 49x + -25x = 3 + 25x + -25x Combine like terms: 49x + -25x = 24x 1.5 + 24x = 3 + 25x + -25x Combine like terms: 25x + -25x = 0 1.5 + 24x = 3 + 0 1.5 + 24x = 3 Add '-1.5' to each side of the equation. 1.5 + -1.5 + 24x = 3 + -1.5 Combine like terms: 1.5 + -1.5 = 0.0 0.0 + 24x = 3 + -1.5 24x = 3 + -1.5 Combine like terms: 3 + -1.5 = 1.5 24x = 1.5 Divide each side by '24'. x = 0.0625 Simplifying x = 0.0625
| 3x-7-4x+11=6x-3 | | 12a+12a+7a+7a= | | 40c+8=48c-20 | | -30=-5+5 | | 3x-7-4x+11=6x-7 | | 2f=10 | | 10+5(a-3)=9-2a | | tg(2x)=0.6 | | 2z^2-15z+7=0 | | 7(x-6)=56 | | x^2-10x+6=1 | | 7(3s+4)=133 | | 3z+3z+4z+3+4z+3=132 | | 3f=9 | | 8(2l+8)=112 | | 3x+1+1x+11=180 | | 5*(5*(5*(5+4)+3)+2)+1= | | x+13=111 | | 6k+k-3k+3=19 | | 7h+18=214 | | -2(x+7)=14 | | 2A+2b=bc | | f(2n+1)=f(n)+f(n-1) | | 6x-6=-15 | | (q-9)*4=8 | | (9c+5)(7c-1)=0 | | -10m-11m+13m=16 | | p(x)=2x^3+x^2-49x+8 | | (q-4)*9=8 | | 6j(j+4)=0 | | x+x^2=8.5 | | 1x+10+1x+50=180 |